ANALISIS STRUKTURAL DAN NILAI MORAL DALAM NOVEL KEMBANG ASIH DI PASANTREN KARYA EDYANA LATIEF - I. Nurhasyanah; O. Ropiah (Prodi Pendidikan Bahasa dan Sastra Daerah, 2018)
The purpose of this study is to describe the structure of the story in the novel Kembang Asih di Pasantren and moral values that exist in the novel Kembang Asih di Pasantren. Sources of data in this study is novel Kembang Asih di Pasantren by Edyana Latief. The method used in this research is descriptive analysis. The technique used in this research is the literature study. Based on the results of the research, the structure of the novel Kembang Asih di Pasantren include a theme, a fact the story (plot, character, and background) and the literary devices (title, viewpoints, style, symbolism, and irony). The themes in the novel Kembang Asih di Pasantren are affectionate, tells the love story of three pairs of students in boarding schools that ends with a wedding. Flow used in this novel is the flow of the mixture. There are 28 characters that play a role in this story. Background story background includes space, time, and atmosphere. Background of place is 12, setting the time is 9, and the background of situation are 13. The title of his novel element is the Kembang Asih di Pasantren. Viewing angles are used is a third-person omniscient. The language used by the author in this story the general nature of humor. The symbolism in this novel is a love. The irony in this novel there are 6 events. The moral of the novel Kembang Asih di Pasantren include moral for God, moral human for himself, moral human being for others, moral human for nature, moral human for time, and moral human for getting the outer and inner happiness. Moral for God there are 9, moral human for himself there are 17, moral human being for others there are 10, moral human for nature there are 1, moral human for time there are 5, and moral human for getting the outer and inner happiness there are 3.